(untitled) (Journal of the College of Basic Education, 2023)
If the unity of existence is linked and its full picture is taken in Islamic mysticism at the hands of MohiAl-Din Ibn Arabi (d. 628 AH). This does not mean that he invented it himself. You weren’t thereHis etymological break in the Foucauldian sense of the term, or the emergence of a new turn in the direction of thoughtphilosophical and mystical. We find in the history of Islamic Sufism beginnings that paved the way for the emergence of the theory ofThe unity of existence is an example of what we find from the states of annihilation at al-Bustami (d. 261 AH) and al-Hallaj (d.309 AH). (1)And if the state of the Sufi’s annihilation is the result of his tastes, in the sense that it is unique, private, and temporary, exceptIt was one of the main references for the inauguration and emergence of the theory of unity of existence. And what we find whenIbn Massara in his mystical or esoteric doctrine, or what is called Alabathuglesia Al Nahla (2). representAlso the first roots of this theory (the theory of unity of existence).The Unity of Existence is not limited to Islamic thought only, but also had its pioneers among the thinkers.Philosophers in human thought in general before and after Ibn Arabi are an example of what we find in Eastern thought.ancient, especially among the Indians and the Chinese.Or what we find in Greek philosophy, such as Heraclitus (540 - 475 BC) in his saying of the LogosThe one who organizes the world and his saying that existence is one and that the parts are manifestations and the phenomena are for him (3) and likewiseAt Parmenides 540) -? BC) in transcending the world of phenomena and saying that existence and the one are saidat the end of a number, and the true existence is the fixed mental existence, and as for the phenomena, they are pure illusion (4). Likewise, we find the thought - the idea of the unity of existence - at Spioz, for example in modern philosophy.In his saying that nature is natural and nature is imprinted, and that existence is one (5), as well as when Hegel inHis saying, by the all-seeing spirit that manifests itself in the phenomena in a dialectical manner, the reality of existence is one, and this